Modulation of the Redox Potential and Electron/Proton Transfer Mechanisms in the Outer Membrane Cytochrome OmcF From Geobacter sulfurreducens - Teixeira, Liliana R.; Cordas, Cristina M.; Fonseca, Marta P.; Duke, Norma E. C.; Pokkuluri, Phani Raj; Salgueiro, Carlos A. (Frontiers in Microbiology, 2020)
The monoheme outer membrane cytochrome F (OmcF) from Geobacter sulfurreducens plays an important role in Fe(III) reduction and electric current production. The electrochemical characterization of this cytochrome has shown that its redox potential is modulated by the solution pH (redox-Bohr effect) endowing the protein with the necessary properties to couple electron and proton transfer in the physiological range. The analysis of the OmcF structures in the reduced and oxidized states showed that with the exception of the side chain of histidine 47 (His47), all other residues with protonatable side chains are distant from the heme iron and, therefore, are unlikely to affect the redox potential of the protein. The protonatable site at the imidazole ring of His47 is in the close proximity to the heme and, therefore, this residue was suggested as the redox-Bohr center. In the present work, we tested this hypothesis by replacing the His47 with non-protonatable residues (isoleucine – OmcFH47I and phenylalanine – OmcFH47F). The structure of the mutant OmcFH47I was determined by X-ray crystallography to 1.13 Å resolution and showed only minimal changes at the site of the mutation. Both mutants were 15N-labeled and their overall folding was confirmed to be the same as the wild-type by NMR spectroscopy. The pH dependence of the redox potential of the mutants was measured by cyclic voltammetry. Compared to the wild-type protein, the magnitude of the redox-Bohr effect in the mutants was smaller, but not fully abolished, confirming the role of His47 on the pH modulation of OmcF’s redox potential. However, the pH effect on the heme substituents’ NMR chemical shifts suggested that the heme propionate P13 also contributes to the overall redox-Bohr effect in OmcF. In physiological terms, the contribution of two independent acid-base centers to the observed redox-Bohr effect confers OmcF a higher versatility to environmental changes by coupling electron/proton transfer within a wider pH range.